The expert with the justice = El perito con la justicia - Gil Carrillo, Francisco; Hortelano Anguita, Miguel Angel; Caldentey Gallardo, Eduardo (Building & Management, 2018)
Abstract The expert evidence is a transmission of information that the expert makes to the judge or to a third party, in the form of an opinion so that he can assess facts or relevant circumstances in a given process. It is regulated in the LEC [1] (January 7, 2000) in articles 335 and 352. Thus the expert is configured as that person who has specific knowledge of which the court lacks and that are necessary for a proper evaluation of the process. The expert is a subject that by definition must be extraneous to the process and to the facts [2] The expert must not possess legal knowledge but if he knows the protocol that is used in judiciary proceedings in which he intervenes, in addition to have the knowledge, at least of the specialty that proves with his title and that are accurate in the test. The expert must be aware of the importance of his work in the judicial process and the value of his evidence, which can unbalance the balance of justice, with the damages and benefits inherent in the respective parties. Resumen La prueba pericial es una transmisión de información que los perito realizan al juez o a un tercero, en forma de dictamen para que pueda valorar hechos o circunstancias relevantes en un determinado proceso. Se encuentra regulada en la LEC [1] (7 enero de 2000) en sus artículos 335 y 352. Así el perito se configura como aquella persona que dispone de conocimientos específicos de los que el tribunal carece y que resultan necesarios para una correcta evaluación del proceso. El perito es un sujeto que por definición previa debe ser ajeno al proceso y a los hechos [2]. El perito no debe de poseer conocimientos jurídicos, pero si conocer el protocolo que se utiliza en los procedimientos judiciales en los que interviene, además de tener conocimientos, al menos de la especialidad que acredite con su título y que sean precisos en la prueba [2]. El perito ha de ser consciente de la trascendencia que tiene su trabajo en el proceso judicial y el valor de su prueba, que puede desequilibrar la balanza de la justicia, con lo perjuicios y beneficios inherentes a las respetivas partes.